Towards the construction of housing indicators: principles and criteria from the rights approach - Canestraro, María Laura; Zulaica, María Laura; Arenaza, María Soledad (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2019)
The New Urban Agenda agreed upon at Habitat III highlights the need to redefine public policies for Latin American cities. One of the main topics of discussion is linked to the problem of access to land. In this framework, the Urban Prosperity Index gains importance by incorporating housing indicators aimed at urban sustainability. However, it does not include the land component and qualitative criteria that would allow, from a rights-based perspective, to make diagnosis and urban intervention more complex. This paper elaborates upon the proposal of construction of housing indicators by defining principles and useful criteria to monitor compliance with public policies.